Full-scale removal of arsenate and chromate from water using a limestone and ochreous sludge mixture as a low-cost sorbent material - Cederkvist, Karin (Water environment research : a research publication of the Water Environment Federation, 2010)
The oxyanions arsenate (AsO4(3-)) and chromate (CrO4(2-)) are major freshwater contaminants. Arsenate is a problematic contaminant in drinking water reservoirs, and chromate limits the use of urban stormwater runoff. High-capacity, low-cost, energy-efficient treatment technologies are required for the removal of these toxic anions from freshwater sources. Using a 50-m-long dual porosity filter, with limestone as filtering grains, treating stormwater runoff from Copenhagen, Denmark, we tested if addition of the waste product ochreous sludge can improve the removal of arsenate (As) and chromate (Cr) without compromising the calcite's removal affinity fowards metallic cations. Upon on-site embedding of the ochreous sludge, removal of arsenic and chromium was improved greatly, and copper (Cu) removal remained high. Steady-state effluent concentrations were reduced from 31 to 2 microg As/L, 127 to 1.5 microg Cr/L, and 18 to 9.6 microg Cu/L upon mixing with the ochreous sludge. Limestone-ochreous sludge represents a promising low-cost oxyanion and cation sorbent operating at neutral pH without pH control